Assessment Nursing Knowledge about Cardiopulmonary Resuscitation in the Cardiac Care Unit - Ali, Zainab H.; Hussein, Hwra Ali (Journal of Science in Medicine and Life, 2025)
Background: Cardio-pulmonary resuscitation (CPR), in many emergency situations, is an essential life- saving technique. It is a vital skill that all members of the medical community, including students, should learn since it can save a patient's life if it is performed early. Objective: To assess nursing knowledge about cardio- pulmonary resuscitation. Methodology: A descriptive study design was used to assess nursing knowledge about cardio-pulmonary resuscitation for the period from (Octoper 28th, 2024 to April 28th, 2025). Results: The study shows that the level of nursing knowledge about cardio-pulmonary resuscitation was fair at the mean of score 1.5. Conclusions: The study revealed that more than half of the participants had moderate knowledge about CPR. Recommendations: Training courses should be conducted regularly and periodically to develop the nursing staff working in critical care settings, including basic and necessary information on cardiopulmonary resuscitation (CPR) and advanced cardiac life support.